Effectiveness and Safety of Mechanical Thrombectomy in Large-Vessel-Occlusion Mild Stroke: Insights from the ASSIST Registry - Hohenstatt, Sophia; Vollherbst, Dominik F.; Miralbés, Salvador; Naravetla, Bharath; Spiotta, Alejandro; Loehr, Christian; Martínez-Galdámez, Mario; McTaggart, Ryan; Defreyne, Luc; Vega, Pedro; Zaidat, Osama O.; Jenkins, Paul; et al. (American Journal of Neuroradiology, 2024)
BACKGROUND AND PURPOSE: Mechanical thrombectomy (MT) is effective for acute ischemic stroke, yet its indication in mild stroke remains unclear. This study evaluates MT's effectiveness and safety in low NIHSS patients and assesses different MT strategies' impact on procedural success and clinical outcomes.MATERIALS AND METHODS: Data from the ASSIST Registry were analyzed, categorizing patients with large vessel occlusion of the anterior circulation into mild (NIHSS≤5) and moderate-severe (NIHSS>5) stroke groups. Baseline characteristics, procedural parameters, angiographic and imaging outcomes, clinical outcomes, and safety endpoints were compared. Within the mild stroke subgroup, outcomes were compared between different MT techniques.RESULTS: Among 1360 patients with LVO, 122 had minor ischemic strokes (9%). Mild stroke patients had high rates of excellent functional outcomes (mRS 0-1) at 90 days (77.1%) and functional independence (mRS 0–2) (85.7%). Procedural success rates were similar between NIHSS groups, while safety outcomes, except mortality, were comparable. No statistically significant differences were observed in treatment techniques within the mild stroke subgroup. Significant predictors of early neurological deterioration (END) in mild stroke patients were the total number of passes (OR 1.49, 95% CI 1.01 – 2.19, P=.04) and total procedure time (OR 1.02, 95% CI 1.01 – 1.04, P=.01). Patients with END were more likely to have an unfavorable functional outcome (mRS 3-6) at 90 days (89% vs. 6%, P<0.001).CONCLUSIONS: MT is effective and safe in mild stroke patients. Procedural success did not vary among MT techniques in mild stroke. The total number of passes predicts END, which suggests a causal pathway that requires further exploration.ABBREVIATIONS: AIS = acute ischemic stroke; BMT = best medical treatment; DA = direct aspiration; END = early neurological deterioration; EVT = endovascular treatment; LVO = large vessel occlusion; MT = mechanical thrombectomy; SAEs = serious adverse events; sICH = symptomatic intracranial hemorrhage; SR = stent retriever.